Islamic Education Curriculum in the Era of Society 5.0: Between Challenges and Innovation - Suhendi, Saca (GoAcademica Research & Publishing, 2024)
In the era of Society 5.0, Islamic education faces major challenges in adapting its curriculum to rapid technological developments. Changes in the need for skills and competencies require the Islamic education system to be more adaptive to digitalization without ignoring its fundamental values. However, the gap between the traditional curriculum and the demands of the digital era is still a significant obstacle to implementing innovative Islamic education. This study aims to analyze the transformation of the Islamic education curriculum in the era of Society 5.0, by highlighting the challenges and innovations that can be applied to improve learning effectiveness. The research method used in this study is a qualitative approach, by collecting data from various relevant sources, such as previous research and academic studies. The analysis was carried out descriptively to describe the pattern of transformation, obstacles faced, and innovative strategies that can be applied in the development of Islamic education. The results of the study show that Islamic education needs to integrate technology into its learning system to improve the quality and relevance of the curriculum. Although there are obstacles in the application of technology, innovations such as the use of artificial intelligence, blended learning, and data-based analysis can be effective solutions. With the right strategy, Islamic education can not only adapt to the digital era but also maintain its role in building the character and morals of the Muslim generation.